First report of a Dengue outbreak in Balsas, Amazonas, Peru, during 2021 and 2022.: Primer reporte de un brote de dengue en Balsas, Amazonas, Perú, durante 2021 y 2022 - Ramírez Orrego, Lourdes; Rojas Muro, Luis Martin; Campos, Christian J.; Gutiérrez de Carrillo, Carmen Ines; Chenet, Stella M.; Gonzales Cornejo, Lizandro (Revista de la Facultad de Medicina Humana, 2023)
Introduction: The increase in dengue cases in Amazonas is a risk to public health. In 2021, Balsas reported a dengue outbreak for the first time. Methodology: The population included patients who met the case definition between December 2021 and February 2022. Identification of serotypes will be reduced by multiplex qRT-PCR. Results: 72 patients were identified, of which 53 (74%) were confirmed by serology (Ag NS1). The predominant serotype was DENV-2 (94%), and 6% was DENV-1. Patients between 19 and 45 years old presented the highest percentage of cases (59%). The most frequent symptoms were fever, headache, myalgia and arthralgia; 23% presented severe abdominal pain. Conclusion: This was the first confirmed dengue outbreak in the Balsas district, with DENV-2 being the main cause of the outbreak, highlighting the need to improve surveillance in areas without autochthonous transmission of the disease.